Activity profile and physical demands of football referees and assistant referees in international games - Krustrup, P.; Helsen, W. F.; Randers, M. B.; Christensen, J. F.; MacDonald, C.; Natal Rebelo, A.; Bangsbo, J. (Journal of Sports Sciences, 2009)
Time-motion analyses and physiological measurements were performed to investigate the physiological demands of football referees (n = 15) and assistant referees (n = 15) in international games and to examine whether high-intensity running (HIR) correlates to the referees' ability to keep up with play. Total distance covered (10.27 ± 0.90 vs. 6.76 ± 0.83 km) and HIR (1.92 ± 0.58 vs. 0.97 ± 0.22 km) was higher (P < 0.05) for referees than assistant referees, while sprinting distance was not different. Referees covered 0.89 ± 0.37 km by backwards running and assistant referees covered 1.54 ± 0.66 km by sideways running. Mean heart rate was higher (P < 0.05) for referees than assistant referees (150 ± 3 vs. 123 ± 3 b.p.m.), whereas blood lactate was not different. Backwards/sideways running decreased (P < 0.05) from the first to the last 15-min period for referees (49%) and assistant referees (42%), whereas HIR was unaltered. HIR was inversely correlated with the five highest distances from infringements in both halves (r = -0.60 and -0.58, P < 0.05). In conclusion, international match officials carry out an important amount of HIR throughout games, while low-intensity and unorthodox running activities are reduced during games. Referees performing the most high-intensity work are better to keep up with play. The match activities differ significantly between referees and assistant referees, which should be considered in training and testing procedures.